2004
DOI: 10.3171/spi.2004.1.2.0228
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous vertebroplasty for the treatment of burst fractures

Abstract: ✓ Percutaneous vertebroplasty is a useful procedure for patients with vertebral osteoporotic compression fractures; however, there has been no mention in the literature of the use of percutaneous vertebroplasty for the treatment of traumatic spinal fractures. The authors report the case of a 33-year-old man who harbored L-1, L-2, and L-5 burst fractures sustained in a work-related accident. The patient was successfully treated by percutaneous vertebroplasty with polymethylmeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 9 publications
0
27
0
2
Order By: Relevance
“…[24][25][26] Several small studies have demonstrated encouraging results for the use of vertebroplasty for the treatment of painful nonosteoporotic vertebral compression fractures. 2,5 A small study of patients with traumatic compression fractures found a decrease in pain in all subjects with limited extravasation of cement, all of which was asymptomatic. 3 Our results confirmed these results with a larger patient population and for a longer duration of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] Several small studies have demonstrated encouraging results for the use of vertebroplasty for the treatment of painful nonosteoporotic vertebral compression fractures. 2,5 A small study of patients with traumatic compression fractures found a decrease in pain in all subjects with limited extravasation of cement, all of which was asymptomatic. 3 Our results confirmed these results with a larger patient population and for a longer duration of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, the literature regarding the use of vertebroplasty for traumatic, nonosteoporotic, and/or non-neoplastic, compression fractures remains limited, with studies restricted to a small number of patients. [2][3][4][5] The use of vertebroplasty for patients with traumatic vertebral fractures is complicated by the complexity of the injuries and the multifaceted demographics of the patient population itself. 6 Of particular concern is the potential for traumatic vertebral fractures to have more endplate fracturing, leading to increased cement leakage.…”
mentioning
confidence: 99%
“…Vertebroplasty, involving the percutaneous injection of liquid bone cement into the fracture site, has only recently been considered as a possible alternative to traditional surgical treatment of burst fractures, and there is still only a limited number of clinical case studies reporting its use 1,9,10,15,26. These studies concluded that the treatment has the potential to reduce reliance on painkillers and increase mobility 26…”
Section: Introductionmentioning
confidence: 99%
“…Únicamente apreciaron una fuga intradiscal del material de refuerzo (polimetilmetacrilato) a nivel L4-L5, sin clínica asociada, reiniciando el paciente las actividades de la vida diaria a los tres meses del procedimiento 15 . Del mismo modo, Burton et al 10 establecieron la posibilidad del uso del refuerzo vertebral mediante vertebroplastia en las fracturas en estallido de origen osteoporótico, a raíz de la experiencia comunicada por Nakano et al 55 .…”
Section: Discussionunclassified